Arcjet plasma temperature estimation in thruster device - V. I. Gorbunkov; V. V. Kositsin; V. I. Ruban; V. V. Shalay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The kinetic theory of gases methods has been used to evaluate plasma arc parameters in the arcjet thruster device. It greatly means the compression process in adiabatic character and gas temperature increasing for excited atoms Boltzmann distribution over the energy levels. Using argon gas for arcjet working process carring out, the way of gas temperature eveluation is offered. The results of the study can be use in the spacecraft arcjet development